2023
DOI: 10.3201/eid2903.221417
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Retrospective Study of Vascular Infections and Endocarditis Caused by Campylobacter spp., France

Abstract: The incidence of campylobacteriosis has substantially increased over the past decade, notably in France. Secondary localizations complicating invasive infections are poorly described. We aimed to describe vascular infection or endocarditis caused by Campylobacter spp. We included 57 patients from a nationwide 5-year retrospective study on Campylobacter spp. bacteremia conducted in France; 44 patients had vascular infections, 12 had endocarditis, and 1 had both cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…Relapse (defined by > 1 new positive blood culture with Campylobacter spp. after clinical sign resolution and apyrexia or negative control blood culture) occurred in 8 % of cases and was associated with delayed initiation of an efficient antimicrobial therapy, diabetes, and coexistence of an osteoarticular location [ 8 ]. In our patient, relapse seems indeed to be the most likely hypothesis to explain the secondary CIED infection, although we cannot completely rule out reinfection as strain sequencing could not have been performed.…”
Section: Discussionmentioning
confidence: 99%
“…Relapse (defined by > 1 new positive blood culture with Campylobacter spp. after clinical sign resolution and apyrexia or negative control blood culture) occurred in 8 % of cases and was associated with delayed initiation of an efficient antimicrobial therapy, diabetes, and coexistence of an osteoarticular location [ 8 ]. In our patient, relapse seems indeed to be the most likely hypothesis to explain the secondary CIED infection, although we cannot completely rule out reinfection as strain sequencing could not have been performed.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly detected cause of Campylobacter bacteremia is C. fetus ( 5 , 6 ). However, cohorts or large case series exclusively involving patients with C. fetus bacteremia remain scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients with C. fetus bacteremia, one third exhibited secondary localizations with a predilection for vascular infections. A recent multicenter study in France (252 patients with C. fetus bacteremia) found that 11.5% patients had vascular localization and 4.4% had endocarditis ( 6 ). In our study population, we found more vascular localizations but less endocarditis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations